PENGARUH PROSES KOGNITIF TERHADAP PERKEMBANGAN BAHASA - M. Wisnu Nurdiyanto; Nurul Khairatul Fadliani; Silvina Noviyanti (STKIP Subang, 2025)
This study aims to analyze how cognitive processes influence language development, particularly in the aspects of intonation, word choice, and gesture. The research problem focuses on how mental mechanisms such as attention, working memory, conceptual organization, and emotional regulation shape an individual’s linguistic performance. This study employed a descriptive qualitative method with interviews as the primary instrument. The data were obtained from several informants who described how their thoughts, knowledge, emotions, and social interactions affect the way they speak in daily communication. The findings indicate that cognitive processes play a significant role in determining verbal expression: individuals adjust their language style according to their understanding of the topic, their emotional state, and the social status of their interlocutor. Intonation becomes softer or firmer depending on emotional control and social context, while word choice is influenced by cognitive maturity and environmental habits. Furthermore, gestures function as extensions of cognitive-motor processes that help clarify messages, but can appear impolite when self-regulation decreases. These findings support Piaget’s theory that language reflects cognitive structures and Vygotsky’s view that language is shaped through social mediation before being internalized as cognitive tools. Overall, this research provides empirical evidence that language, cognition, and social interaction are interrelated components that shape an individual’s communicative behavior.